Prospective validation of a new imaging scorecard to assess leptomeningeal metastasis: A joint EORTC BTG and RANO effort. Issue 10 (14th February 2022) - Le Rhun, Emilie; Devos, Patrick; Winklhofer, Sebastian; Lmalem, Hafida; Brandsma, Dieta; Kumthekar, Priya; Castellano, Antonella; Compter, Annette; Dhermain, Frederic; Franceschi, Enrico; Forsyth, Peter; Furtner, Julia; et al.
Abstract: Background: Validation of the 2016 RANO MRI scorecard for leptomeningeal metastasis failed for multiple reasons. Accordingly, this joint EORTC Brain Tumor Group and RANO effort sought to prospectively validate a revised MRI scorecard for response assessment in leptomeningeal metastasis. Methods: Coded paired cerebrospinal MRI of 20 patients with leptomeningeal metastases from solid cancers at baseline and follow-up after treatment and instructions for assessment were provided via the EORTC imaging platform. The Kappa coefficient was used to evaluate the interobserver pairwise agreement. Results: Thirty-five raters participated, including 9 neuroradiologists, 17 neurologists, 4 radiation oncologists, 3 neurosurgeons, and 2 medical oncologists. Among single leptomeningeal metastases-related imaging findings at baseline, the best median concordance was noted for hydrocephalus (Kappa = 0.63), and the worst median concordance for spinal linear enhancing disease (Kappa = 0.46). The median concordance of raters for the overall response assessment was moderate (Kappa = 0.44). Notably, the interobserver agreement for the presence of parenchymal brain metastases at baseline was fair (Kappa = 0.29) and virtually absent for their response to treatment. 394 of 700 ratings (20 patients x 35 raters, 56%) were fully completed. In 308 of 394 fully completed ratings (78%), the overall response assessment perfectly matched the summary interpretation of the single ratings as proposed in the scorecard instructions. Conclusion: This study confirms the principle utility of the new scorecard, but also indicates the need for training of MRI assessment with a dedicated reviewer panel in clinical trials. Electronic case report forms with "blocking options" may be required to enforce completeness and quality of scoring.